2005
DOI: 10.1016/s0004-9514(05)70039-8
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the physiotherapy profession in New South Wales (1975–2002)

Abstract: This was the first study known to the authors exploring workforce data from the New South Wales Physiotherapists Registration Board over several decades. Labour force statistics were examined from various data sources over the years 1975 to 2002. The results indicate that the demographics and working patterns of physiotherapists in New South Wales have remained remarkably stable over time. The workforce continues to grow, however the growth rate has decreased markedly with only a 2.3% increase from 2001 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…J Orthop Sports Phys Ther 2012;42 (2) 2,36 and are expected to apply manual forces competently to minimize the potential for adverse effects. 7,18 There is moderate evidence of the effectiveness of spinal mobilization for treating low back pain, which is supported by several systematic reviews and clinical guidelines.…”
Section: T T Conclusionmentioning
confidence: 99%
“…J Orthop Sports Phys Ther 2012;42 (2) 2,36 and are expected to apply manual forces competently to minimize the potential for adverse effects. 7,18 There is moderate evidence of the effectiveness of spinal mobilization for treating low back pain, which is supported by several systematic reviews and clinical guidelines.…”
Section: T T Conclusionmentioning
confidence: 99%
“…While the private sector increased its contribution over the 3-year period, its average contribution was only 14%. Given that in 2001 58.6% of registered physiotherapists in NSW worked in the private sector, 12 the contribution from the private sector is inadequate. This challenge has also been documented in medicine.…”
Section: Need For Additional Placement Sitesmentioning
confidence: 99%
“…11 In NSW, 58.6% of registered physiotherapists work in the private health care sector. 12 We aim to provide students with experiences in the private sector, however, given only 14% of clinical placements are provided by the private sector, it is unlikely all students will have an experience in this sector.…”
mentioning
confidence: 99%
“…Although attrition rates have not been quantified in the literature, this has been determined by the limited increase in workforce participation over time and a decrease in professional life expectancy of male physiotherapists. 3,4 Anderson et al reported that whilst there was an increase in males entering the profession, male physiotherapists were not being retained, as there was no increase in the modal age of male physiotherapists over time. 3 Changes in the treatment population are also impacting on the physiotherapy workforce.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Anderson et al reported that whilst there was an increase in males entering the profession, male physiotherapists were not being retained, as there was no increase in the modal age of male physiotherapists over time. 3 Changes in the treatment population are also impacting on the physiotherapy workforce. Service provision is becoming more stretched in areas such as aged care and public health due to the ageing population.…”
Section: Introductionmentioning
confidence: 99%